1989
DOI: 10.1007/bf00153488
|View full text |Cite
|
Sign up to set email alerts
|

Increased muscle tension and reduced elasticity of affected muscles in recent-onset Graves' disease caused primarily by active muscle contraction

Abstract: Abstract. In 3 patients with Graves' disease of recent onset, length-tension diagrams were made during surgery for squint under eyedrop anesthesia. The affected muscles were found to be very stiff when the other eye looked straight ahead. It was expected that these stiff muscles would be able to shorten to some extent but would be unable to lengthen, due to fibrosis of the muscle. We found that the affected muscles did not shorten very much when the other eye looked into the field of action of the muscle. Unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…As the increase was more pronounced in the early stages than in the late stages of TAO, it could be caused by an elevated eye muscle contractility that was described as a characteristic finding in inflammatory active TAO by Simonsz & Kommerell (1989). The authors found the contractile properties to be substantially altered in such individuals leading to a higher contractile activity.…”
Section: Discussionmentioning
confidence: 94%
“…As the increase was more pronounced in the early stages than in the late stages of TAO, it could be caused by an elevated eye muscle contractility that was described as a characteristic finding in inflammatory active TAO by Simonsz & Kommerell (1989). The authors found the contractile properties to be substantially altered in such individuals leading to a higher contractile activity.…”
Section: Discussionmentioning
confidence: 94%
“…2003). Simonsz & Kommerell (1989) supplied evidence for the notion that, in the early stages of TAO, it is the contracture of eye muscles that creates increased stiffness, compared with normal eye muscle. Our results of increased steady‐state tension in patients with mild, active TAO might then be explained by increased muscle tonus but not by reduced elasticity from muscle inflammation and fibrosis, as in pronounced, active and longstanding, inactive TAO.…”
Section: Discussionmentioning
confidence: 99%
“…The dose effect is higher in comparison to squint surgery for concomitant squint due to increased muscle tension and low elasticity in Grave's orbitopathy patients [ 22 ] (see Tables 21.1 and 21.2 ). Respecting the arc of contact, squint angles up to 15-17.5° (30-35 pdpt) can be corrected with a single inferior recession.…”
Section: Resulting In Hypotropiamentioning
confidence: 96%